PROFIL PENYELENGGARAAN KETERAMPILAN KECAKAPAN HIDUP (LIFE SKILL) BAGI ANAK TUNAGRAHITA - Nia Yolisa Fitri (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstrack: The background of this research is some students with mental retardation that attend learning process of Life Skills of vocational program at the workshop skills. This study was conducted to look at the model of learning in the implementation of life skills of tataboga subject watter and to investigate the role of teachers in helping organizing the life skills of tataboga and also to know the constraints faced in the implementation of life skill of tataboga. This research was conducted in SLBN 2 Padang, on Profile of Implementation Life Skills in child mental retardation. Kata-kata kunci: Anak Tunagrahita; Life Skill; Tataboga.